PENINGKATAN AKTIVITAS PEMBELAJARAN ILMU PENGETAHUAN ALAM DENGAN METODE DEMONTRASI KELAS III SEKOLAH DASAR NEGERI 14 TAUK - F34211123, Suparjo; ., Sukmawati; ., Zainuddin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2013)
Abstract: the use of demonstration Method To Improve activity of learning to thelearners in teaching natural sciences class III 14 Tauk elementary school. The problem in this research is,